Memorandum of understanding between Universiti Teknologi MARA and RVS College of Engineering & Technology Coimbatore, Tamilnadu, India / Fakulti Kejuruteraan Elektrik - Universiti Teknologi MARA, Fakulti Kejuruteraan Elektrik (Universiti Teknologi MARA (UiTM), 2019)
UiTM and RVS College shall endeavour to strengthen, promote and develop academic, cultural and research co-operation on the basis of equality and mutual benefit.